2019
DOI: 10.3390/v11070612
|View full text |Cite
|
Sign up to set email alerts
|

Different Pathogenicity and Transmissibility of Goose-Origin H5N6 Avian Influenza Viruses in Chickens

Abstract: Highly pathogenic avian influenza H5N6 viruses have been circulating in poultry in Asia since 2013 and producing serious diseases in chickens. Here, we analyzed the genetic properties of 10 H5N6 subtypes AIVs from geese in 2015–2016 in Guangdong province. Phylogenic analysis showed that all HA genes of the 10 viruses belonged to clade 2.3.4.4, and their genes including HA, PA, PB1, M, NP, and NS all derived from Mix-like 1 (CH, VN, LS). Their PB2 genes come from Mix-like 2 (CH, VN, JP). The NA genes were class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Significant mutations may contribute to the evolution, the host specificity and pathogenicity of influenza viruses (Carrat & Flahault, 2007; Shao et al., 2017). Similar to the previous studies (Kwon et al., 2018; Lee et al., 2017; Mei et al., 2019; Mine et al., 2019; Qu et al., 2019; Song et al., 2019; Sun et al., 2018; Uchida et al., 2019), all of the four H5N6 viruses in our study might be highly pathogenic to chickens, which contained a series of multiple basic amino acids in the HA cleavage, and they also could transmit to contact chickens. However, our viruses exhibited high virulence in mice and could replicate lungs, brains, spleens and kidneys.…”
Section: Discussionsupporting
confidence: 90%
“…Significant mutations may contribute to the evolution, the host specificity and pathogenicity of influenza viruses (Carrat & Flahault, 2007; Shao et al., 2017). Similar to the previous studies (Kwon et al., 2018; Lee et al., 2017; Mei et al., 2019; Mine et al., 2019; Qu et al., 2019; Song et al., 2019; Sun et al., 2018; Uchida et al., 2019), all of the four H5N6 viruses in our study might be highly pathogenic to chickens, which contained a series of multiple basic amino acids in the HA cleavage, and they also could transmit to contact chickens. However, our viruses exhibited high virulence in mice and could replicate lungs, brains, spleens and kidneys.…”
Section: Discussionsupporting
confidence: 90%
“…They demonstrate relevant host-virus features in chickens and mice, including systemic replication and contact transmission between chickens, and upregulation of PRR in different organs in chicken and mice. Mei et al [6] also reveal that goose-origin H5N6 avian influenza viruses have different pathogenicity and transmissibility in chickens. Yu et al [7] present a comparative analysis between highly and low pathogenic H7N9 AIV strains.…”
mentioning
confidence: 98%
“…Changes at these sites suggest that the ability of the virus to infect humans across species may be enhanced. Recent studies have found that changes in some glycosylation sites of HA protein play an important role in virus proliferation, infectivity and transmission [31,32]. The glycosylation sites of the HA gene of the virus strain in this study were between 8 and 9.…”
Section: Discussionmentioning
confidence: 53%